A Juridical Study of the Death Penalty from a Human Rights Perspective - Arifullah, A. (Manunggal Halim Jaya, 2024)
This research aims to explore the legal and human rights implications of capital punishment, particularly in relation to the right to life as enshrined in international human rights law. The study critically examines the compatibility of the death penalty with contemporary human rights principles, focusing on its application across different legal systems. A qualitative research methodology, utilizing a systematic literature review, was employed to analyze existing scholarly works, legal documents, human rights reports, and case law related to the death penalty. The research identifies key themes such as the ethical concerns surrounding the irreversible nature of capital punishment, its lack of deterrent effect, and the racial and socioeconomic biases inherent in its application. Additionally, the study investigates the psychological and social consequences of capital punishment, including the emotional toll on both the condemned individuals and society. The findings reveal that while some countries continue to justify the death penalty, a growing global trend towards abolition is evident, fueled by concerns over human rights violations and the risks of wrongful convictions. Furthermore, the research supports the argument that the death penalty is increasingly incompatible with modern human rights standards, particularly as international legal frameworks continue to evolve. This study contributes to the broader debate on capital punishment, offering insights into its ethical, legal, and social dimensions, and calls for continued advocacy for its abolition in favor of more humane forms of justice.